2016
DOI: 10.21927/ijnd.2014.2(3).116-125
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat sosial ekonomi tidak berhubungan dengan kurang energi kronis (KEK) pada ibu hamil

Abstract: Background: Chronic energy defi ciency (CED)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
1
0
5
Order By: Relevance
“…Mothers also need a high energy intake because the workload that is done everyday is very much to do homework such as taking care of the house, children, and husband. [10][11][12] In this study, family income provides a significant difference in the incidence of CED in pregnant women. This is in accordance with research conducted by Mahirawati (2014), which revealed a significant corellation between monthly income and the incidence of CED in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers also need a high energy intake because the workload that is done everyday is very much to do homework such as taking care of the house, children, and husband. [10][11][12] In this study, family income provides a significant difference in the incidence of CED in pregnant women. This is in accordance with research conducted by Mahirawati (2014), which revealed a significant corellation between monthly income and the incidence of CED in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Ibu hamil merupakan suatu kelompok yang paling rawan terhadap masalah gizi karena dapat mempengaruhi tumbuh kembang janin yang dikandung. Kesehatan dan status gizi ibu selama kehamilan merupakan peluang besar bagi janin yang dikandung akan baik dan keselamatan ibu ketika melahirkan akan terjamin (Indriany et al, 2016). Masalah gizi di Indonesia merupakan salah satu penyebab tidak langsung terjadinya kematian ibu dan anak.…”
Section: Pendahuluanunclassified
“…Jika pendapatan yang diterima oleh keluarga hanya cukup untuk membeli makanan, maka jenis makanan yang dikonsumsi sebagai sumber kalori mayoritas ada dalam bentuk karbohidrat yang dapat memengaruhi asupan gizi (PanaI, 2013). Menurut Engka (2013) ketersediaan pangan dipengaruhi oleh produksi pangan dan pendapatan yang menentukan tingkat pembelian makanan (Engka, 2013;Indriany et al, 2016). Tingkat sosial ekonomi keluarga juga mempengaruhi kualitas makanan yang dikonsumsi sehingga wanita hamil yang tidak dapat mengkonsumsi makanan dengan harga yang cukup tinggi, seperti daging, ikan, susu dan protein hewani lainnya dapat mengalami KEK (Fall et al, 2003;Najoan & Manampiring, 2010) .…”
Section: Pembahasanunclassified